[Untitled article] - Gagné, Jean-H. (Relations industrielles / Industrial Relations, 1952)
The awards studied under the present heading have been rendered during the months of March, April, May and June of this year. The points which we found to be of most interest in these awards are covered under the various subjects mentioned.